Ethics and contemporary politics in Latin America - Mendieta Toledo, Lenin Byron (2023)
The essay goes through several territories, all of them supported by politics and ethics. Its objective was to understand contemporary Latin American politics based on ethics through a bibliographical sweep and hermeneutic interpretation. Thus, from this sweep, we will land with our position in other territories that will read this narrative. The method used documentary or bibliographic reviews and hermeneutics to interpret the discourse. Authors were taken into account to build a coherent epistemological path. The conclusions reached are that the right needs the left to be able to argue its existence and that ethics and morals can make a political system work. Furthermore, the ideologies of some social movements lack foundation, so they are used by power groups to alienate and manipulate them, and Latin America needs to decolonize, and a South episteme must be built.